Enhancing implementation of a standardized initial assessment for demand management in outpatient emergency care in Germany: a quantitative process evaluation - Breckner, Amanda; Roth, Catharina; Szecsenyi, Joachim; Wensing, Michel (BMC medical informatics and decision making, 2021)
Inadequate assessment of the severity and urgency of health problems is one of the factors contributing to unnecessary emergency department visits. A software-based instrument for standardized initial assessment (SmED) aims to support healthcare professionals and steer patients to the appropriate source of care. The aim of this study was to evaluate the implementation process of SmED based on the point of view of users in order to facilitate sustainable implementation.